Energetics of the Southern Ocean Mode - Jüling, A.; Viebahn, J.P. (Jan); Drijfhout, S.S.; Dijkstra, H.A. (Journal of Geophysical Research: Oceans, 2018)
Recently, multidecadal variability in the Southern Ocean has been found in a strongly eddying global ocean circulation model. In this paper, we study the Lorenz energy cycle of this so-called Southern Ocean Mode (SOM). The Lorenz energy cycle analysis provides details on the energy pathways associated with the SOM. It shows that ocean eddies and the baroclinic energy pathway together with variations in the kinetic energy input by the wind are crucial aspects of the variability. It is also shown how convective mixing, which is induced by the SOM in particular in the Weddell Gyre, is responsible for the large-scale multidecadal variability in Antarctic Bottom Water and Atlantic Meridional Overturning Circulation.